Associations between household solid fuel use, kitchen ventilation, and depressive symptoms among older adults in China: a national cross-sectional study - Tongxu Zhang; Chen Wu; Yuhan Liu; Jingshuang Qin; Xiaojie Pan; Na An; Min Li (Frontiers in Public Health, 2026)
Objective Household solid fuel use has been associated with adverse mental health outcomes among older adults. However, evidence on the association between household solid fuel use and depressive symptoms, particularly with respect to kitchen ventilation conditions and potential geographic differences, remains limited. Methods This cross-sectional study analyzed data from 11,697 participants aged ≥65 years in the 2018 wave of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Household fuel types and kitchen ventilation conditions were ascertained through self-reported data. Depressive symptoms were assessed using the 10-item Center for Epidemiologic Studies Depression Scale (CES-D-10). Multivariable logistic regression models and multiple linear regression models were employed to estimate associations, adjusting for a range of potential confounders. Results Among 11,697 participants, 3,143 (26.87%) exhibited depressive symptoms, and 3,471 (29.67%) reported household solid fuel use. After adjustment for potential confounders, household solid fuel use was associated with higher odds of depressive symptoms compared with clean fuel use (OR = 1.25, 95% CI: 1.09–1.44). Similar results were observed when depressive symptoms were analyzed as a continuous CES-D-10 score (B = 0.57, 95% CI: 0.33–0.82). In exploratory analyses of specific fuel types, charcoal use showed a relatively higher odds estimate; however, this finding was based on a small number of exposed participants ( n = 39) and should be interpreted cautiously. No significant interaction was observed between household fuel type and kitchen ventilation. Joint analysis showed that participants using solid fuels without mechanical ventilation had higher odds of depressive symptoms compared with those using clean fuels with mechanical ventilation (OR = 2.16, 95% CI: 1.63–2.86). Conclusion Household solid fuel use was associated with depressive symptoms among older adults, with joint exposure analyses further indicating differences across fuel use and kitchen ventilation combinations. These findings highlight the potential relevance of household energy and kitchen ventilation to mental health in later life.